The Effect of Novel Promoter Variants in MATE1 and MATE2 on the Pharmacokinetics and Pharmacodynamics of Metformin. Issue 2 (17th October 2012) - Stocker, S L; Morrissey, K M; Yee, S W; Castro, R A; Xu, L; Dahlin, A; Ramirez, A H; Roden, D M; Wilke, R A; McCarty, C A; Davis, R L; Brett, C M; et al.
<x xml:space="preserve">Abstract</x> Interindividual variation in response to metformin, first‐line therapy for type 2 diabetes, is substantial. Given that transporters are determinants of metformin pharmacokinetics, we examined the effects of promoter variants in both multidrug and toxin extrusion protein 1 (MATE1) (g.–66T→C, rs2252281) and MATE2 (g.–130G→A, rs12943590) on variation in metformin disposition and response. The pharmacokinetics and glucose‐lowering effects of metformin were assessed in healthy volunteers (n = 57) receiving metformin. The renal and secretory clearances of metformin were higher (22% and 26%, respectively) in carriers of variant MATE2 who were also MATE1 reference (P < 0.05). Both MATE genotypes were associated with altered post‐metformin glucose tolerance, with variant carriers of MATE1 and MATE2 having an enhanced (P < 0.01) and reduced (P < 0.05) response, respectively. Consistent with these results, patients with diabetes (n = 145) carrying the MATE1 variant showed enhanced metformin response. These findings suggest that promoter variants of MATE1 and MATE2 are important determinants of metformin disposition and response in healthy volunteers and diabetic patients. Clinical Pharmacology & Therapeutics (2013); 93 2, 186–194. doi:10.1038/clpt.2012.210